Debunking stereotypes: librarian character representation in the anime world - Nurpratama, Muhammad Rifky (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2025)
The purpose of this research is to examine the representation of librarian characters in anime according to Stuart Hall's model of representation. Information utilized within the current study is derived from the article "10 Most Iconic Anime Librarians," published on Gamerant.com, which provides the primary source from which ten of the most iconic librarian characters within anime are established. Utilizing a qualitative method facilitated through content analysis, the current study also employs data triangulation through cross-checking relevant anime episodes as well as scholarly journals. The results indicate that protagonists that depict librarians in anime are now being portrayed as multidimensional characters—knowledge guardians, intellectual freedom advocates, and social change agents. Protagonists such as Iku Kasahara and Hamyuts Meseta have high emotional depth and perform active roles that break the stereotypes for librarians. The depictions contribute to the reconfiguration of librarians' social image, especially among the youth. This research makes a significant contribution to media studies, information literacy, and library science by highlighting the significance of progressive and inclusive images in shaping public perceptions of the librarian profession.